Ischemic preconditioning of cadaver donor livers protects allografts following transplantation - Jassem, Wayel; Fuggle, Susan V; Cerundolo, Lucia; Heaton, Nigel D; Rela, Mohamed (Transplantation, 2006)
Ischemic preconditioning (IP) has been shown in animal models to protect livers against ischemia/reperfusion injury. The aim of this clinical study is to investigate whether IP of cadaver livers prior to retrieval confers protection on the allografts. Cadaveric donor livers were subjected to IP prior to retrieval by clamping of the hepatic pedicle for 10 min followed by reperfusion. Biopsies were obtained from the preconditioned (n=9) and control nonpreconditioned (n=14) liver transplants prior to and 2 hr following reperfusion. Cryosections were stained with antibodies against neutrophils and platelets. IP livers were associated with significantly lower serum levels of aspartate aminotransferase (240+/-98 IU/L vs. 382+/-163 IU/L; P>0.016) and lactate (0.81+/-0.07 mmol/L vs. 1.58+/-0.9 mmol/L; P>0.018) 24 hr following transplantation. Furthermore, recipients of IP livers spent a significantly shorter time in the intensive care unit following transplantation compared to those given nonpreconditioned allografts (1 vs. 2.8+/-1.6 days; P=0.0008). Increases in neutrophil infiltration were detected in 6/14 (43%; P=0.022) and in CD41 deposition in 5/14 (36%; P=0.042) of nonpreconditioned livers. However, none of the IP allografts showed any change in the levels of platelets or neutrophil infiltration following transplantation. IP is an effective method of protecting cadaver donor allografts from cold ischemia and subsequent reperfusion injury. IP is also associated with a reduction in the nonspecific inflammatory response.